Pan PPAR agonist IVA337 is effective in prevention and treatment of experimental skin fibrosis. Issue 12 (9th March 2016) - Ruzehaji, Nadira; Frantz, Camelia; Ponsoye, Matthieu; Avouac, Jerome; Pezet, Sonia; Guilbert, Thomas; Luccarini, Jean-Michel; Broqua, Pierre; Junien, Jean-Louis; Allanore, Yannick
Abstract : Background: The pathogenesis of systemic sclerosis (SSc) involves a distinctive triad of autoimmune, vascular and inflammatory alterations resulting in fibrosis. Evidence suggests that peroxisome proliferator-activated receptors (PPARs) play an important role in SSc-related fibrosis and their agonists may become effective therapeutic targets. Objective: To determine the expression of PPARs in human fibrotic skin and investigate the effects of IVA337, a pan PPAR agonist, in in vitro and in vivo models of fibrosis. Methods: The antifibrotic effects of IVA337 were studied using a bleomycin-induced mouse model of dermal fibrosis. The in vivo effect of IVA337 on wound closure and inflammation were studied using an excisional model of wound healing. Results: Low levels of PPARα and PPARγ were detected in the skin of patients with SSc compared with controls. In mice, IVA337 was associated with decreased extracellular matrix (ECM) deposition and reduced expression of phosphorylated SMAD2/3—intracellular effector of transforming growth factor (TGF)-β1. Although the antifibrotic effect of pan PPAR was similar to that of PPARγ agonist alone, a significant downregulation of several markers of inflammation was associated with IVA337. Despite its anti-inflammatory and antifibrotic properties, IVA337 did not interfere with wound closure. In vitro effects of IVA337 included attenuation of transcription of ECM genes and alteration of canonical and non-canonical TGF-β signalling pathways. Conclusions: These findings indicate that simultaneous activation of all three PPAR isoforms exerts a dampening effect on inflammation and fibrosis, making IVA337 a potentially effective therapeutic candidate in the treatment of fibrotic diseases including SSc.